Editorial: After a Last wave of the Pandemic: Towards a Post-COVID Era (Public Policies in Times of Pandemics II) - Farantos, Georgios; Koutsoukis, Nikitas-Spiros (European Scientific Journal, ESJ, 2023)
This is an Editorial in the Special Edition of the European Scientific Journal entitled “After a Last Wave of the Pandemic: Towards a Post-Covid Era” (Public Policies in Times of Pandemics II). It is a great honor for us, the proposal made by the Editorial Team to participate as Guest Editors of this second Special Edition. After the success of the first special edition entitled "public policies in times of pandemics", we decided to continue by publishing a second special edition. Unfortunately, the remarkably distinguished Professor of the University of the Peloponnese Nikitas-Spiros Koutsoukis passed away just before the publication of this volume. This Special Edition is dedicated to the memory of Professor Nikitas-Spiros Koutsoukis.